Why are Firms that Export Cleaner? International Trade and CO2 Emissions - Rikard Forslid; Toshihiro Okubo; Karen Helene Ulltveit-Moe (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper develops a model of trade and CO2 emissions with heterogenous firms, where firms make abatement investments and thereby have an impact on their level of emissions. The model shows that investments in abatements are positively related to firm productivity and firm exports. Emission intensity is, however, negatively related to firms. productivity and exports. The basic reason for these results is that a larger production scale supports more investments in abatement and, in turn, lower emissions per output. We show that the overall effect of trade is to reduce emissions. Trade weeds out some of the least productive and dirtiest firms thereby shifting production away from relatively dirty low productive local firms to more productive and cleaner exporters. The overall effect of trade is therefore to reduce emissions. We test empirical implications of the model using unique Swedish firm-level data. The empirical results support our model.
Keywords: F12; F14; F18; Q56; 330; heterogeneous firms; CO2-emissions; international trade